The Specificity of Myth in Russian Prose of the End of the XX–The Beginning of the XXI Centuries - F.B., Mukhamedova (RA Journal of Applied Research, 2023)
At the end of the 20th century, in world and Russian culture, there is a revival of interest in myth, in the specifics of the mythological worldview. The explanation for this can be found in the judgment of R. Barth, who argued that “the myth, as a living memory of the past, is able to heal the ailments of the present”. In this regard, it is quite clear that the awareness of the crisis of culture as a crisis of civilization, the desire of modern domestic literature to comprehend the crisis phenomena occurring in spiritual, social, cultural life, have also intensified attempts to form a new model of the world that meets modernity and an idea of ​​it through myth.